Childhood actinomycosis. Report of 3 recent cases. Issue 12 (December 1976) - Drake, D P; Holt, R J
Abstract : Three cases of childhood actinomycosis are reported, 2 with the commonest presentation of cervicofacial abscess and the third with a rarely reported superficial chest wall abscess. The importance of prompt bacteriological diagnosis and adequate treatment with surgical drainage and chemotherapy is stressed. Though in adults males are affected more frequently than females, the sexes are probably equally affected in childhood.